Implementation of the Scaffolding Method in Improving Learning Outcomes of Mutual Respect Material at SMP Negeri 1 Gunung Malela - Murianto; Lubis, Afridha Yani; Susanti, Eva; Saragih, Desi Asmiani; Rahimah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the implementation of the scaffolding method in improving learning outcomes of mutual respect material at SMP Negeri 1 Gunung Malela. The scaffolding method was chosen because it provides learning support that is gradual and adjusted to the development of students' abilities, making it easier for them to understand and internalize the values ​​of mutual respect. This study uses a quantitative approach with an experimental design involving grade VIII students as research objects. The instruments used to collect data were learning outcome tests and observations of student interactions during the learning process. The results of the study showed that the implementation of the scaffolding method had a significant positive impact on improving student learning outcomes, both in terms of knowledge about mutual respect material and their attitudes towards others. This improvement is reflected in changes in students' attitudes and better understanding of the importance of mutual respect in everyday life. Based on these findings, it can be concluded that the scaffolding method is effective in improving the quality of learning and shaping students' character. Therefore, it is recommended that the scaffolding method be applied more widely in schools to improve learning outcomes and shape students' character who are more respectful of others